Factors Affecting Auditor's Ability to Detect Fraud - Prameswari, Almira Dian Prameswari; Purwohedi, Unggul; Respati, Dwi Kismayanti (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
This study seeks to investigate the impact of auditor independence, competence, professional skepticism, and time constraints on their ability to detect fraud. This study uses primary data collected from a sample of auditors employed by the East Jakarta-based Public Accounting Firm (KAP) who have obtained permission from the Ministry of Finance and are listed on the official website of the Financial Professional Development Center, Secretariat General Ministry of Finance as of November 2021. 52 respondents were selected using a convenience sampling method for this study. In this study, hypotheses were tested using multiple regression models and SPSS 25. The results indicate that: 1) Independence has a positive impact on the auditor's ability to detect fraud; 2) Competence has no impact on the auditor's ability to detect fraud; 3) Professional skepticism has a positive impact on the auditor's ability to detect fraud; and 4) Time pressure has no impact on the auditor's ability to detect fraud.